Comparison of Synovex-S® and two levels of Revalor-S® in heavy-weight Holstein steers - Gerry L. Kuhl; D.D. Simms; Dale A. Blasi; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1993)
In two field trials, 434 Holstein steers averaging 849 lbs were assigned randomly to three single implant treatments: 1) Synovex- S®, 2) Revalor®-S 120 (120 mg trenbolone acetate (TBA) + 24 mg estradiol), and 3) Revalor®-S 140 (140 mg TBA + 28 mg estradiol). Revalor-implanted steers gained .05 to .10 lb per day faster, but this improvement was not statistically significant (P>.05). Both Revalor-implanted groups produced trimmer carcasses with less (P<.05) backfat than Synovex steers. All other carcass characteristics and beef sensory properties, including taste panel evaluations of tenderness, juiciness, and flavor, were not influenced by implant used.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Synovex; Revalor; Holsteins; Feedlot; Carcass traits